2014
DOI: 10.1002/cjoc.201400361
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chiral α‐Benzyl‐β2‐hydroxy Carboxylic Acids through Iridium‐Catalyzed Asymmetric Hydrogenation of α‐Oxymethylcinnamic Acids

Abstract: An asymmetric hydrogenation of α‐oxymethylcinnamic acids was developed by using chiral spiro phosphine‐oxazoline/iridium complexes as catalysts to prepare β2‐hydroxycarboxylic acids with high reactivity (TON up to 2000) and excellent enantioselectivity (up to 99.5% ee). By using this highly efficient asymmetric hydrogenation as a key step, a concise total synthesis of natural product homoisoflavone (S)‐(+)‐4 was accomplished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A comparison of the optical rotations between the synthetic and natural samples also established the absolute configurations for three (i.e., 1 , 2 , and 4 ) of the four natural homoisoflavonoids. Apart from significant additions to the limited literature precedents12k12m of enantioselective syntheses of these natural products, the present results may serve to define the relationship between the absolute configuration and the sign of the optical rotation when assigning the absolute configurations of closely related homoisoflavonoids (e.g., close analogues of 1 and 2 , with different substituents on the aromatic rings). Any confusion caused by errors in reports of previous NMR spectroscopic data and solvents has also been clarified.…”
Section: Discussionmentioning
confidence: 91%
“…A comparison of the optical rotations between the synthetic and natural samples also established the absolute configurations for three (i.e., 1 , 2 , and 4 ) of the four natural homoisoflavonoids. Apart from significant additions to the limited literature precedents12k12m of enantioselective syntheses of these natural products, the present results may serve to define the relationship between the absolute configuration and the sign of the optical rotation when assigning the absolute configurations of closely related homoisoflavonoids (e.g., close analogues of 1 and 2 , with different substituents on the aromatic rings). Any confusion caused by errors in reports of previous NMR spectroscopic data and solvents has also been clarified.…”
Section: Discussionmentioning
confidence: 91%
“…Two years later, Zhou's group employed the same catalyst ( CAT4 ) in the AH of α-methylaryloxy-cinnamic acids 17 (Scheme 7). 64 Under 6 atm of hydrogen pressure, using Et 3 N as a basic additive in MeOH at 45 °C, eight substrates were hydrogenated with excellent yields (>98% for all) and enantioselectivities (98 to >99% ee). To demonstrate the applicability of this methodology, the authors reported the enantioselective synthesis of a natural ( S )-homoisoflavanone 19 based on the chiral carboxylic acid ( S )- 18e (Scheme 8).…”
Section: Asymmetric Hydrogenation (Ah)mentioning
confidence: 99%
“…However, previously reported catalysts for the asymmetric hydrogenation of α-oxymethylcinnamic acids show only low to moderate enantioselectivity or low yield. With catalyst ( S a )- 3f , high activity (TON up to 2000) and excellent enantioselectivity (96–99.5% ee) were achieved in the hydrogenation of α-oxymethylcinnamic acids . Using this efficient hydrogenation as a key step, we accomplished a concise, enantioselective total synthesis of the natural product homoisoflavone, which has significant antibacterial activity.…”
Section: Asymmetric Hydrogenation Of αβ-Unsaturated Carboxylic Acidsmentioning
confidence: 99%